China's Developing Labor Law - John Bruce Lewis; Bruce L. Ottley (Washington University Law Quarterly, 1982)
This Article will examine China's labor laws and policies generally as well as those specifically applicable to joint ventures.
Keywords: Joint ventures; Labor law; China